Efeitos neurofisiológicos de terapias cognitivas no manejo da dor : revisão sistemática - Nascimento, Simone de Souza (2018)
Background. Cognitive therapies are alternative forms of pain management. Despite the extensive approach regarding the associations between cognitive therapies and health, the clinical applicability of this evidence in the management of pain has not yet been fully elucidated. The objective of this study was to evaluate the efficacy of cognitive therapy in the management of pain and associated symptoms, the patterns of brain activation promoted in the modulation of pain, as well as the methodological quality of the selected articles. Methods: Two systematic reviews of literature on cognitive therapies and pain management were performed to search the databases - MEDLINE, Pubmed, EMBASE, CINAHL, PsycINFO, Science Direct and Scopus - randomized controlled trials examining neurophysiological data of cognitive therapies in patients with chronic pain or healthy individuals exposed to experimental pain. The primary endpoint was pain and neurophysiological changes and the secondary outcomes were anxiety, depression, and quality of life. Results: A total of 406 articles were found, of which 14 met the criteria for inclusion. The results revealed that cognitive therapies reduced the intensity and discomfort of pain, as well as improved pain tolerance and expectancy. In addition, there was improvement of physical and mental health, anxiety, depression and catastrophism. Neuroimaging data revealed distinct patterns of activity, but mainly related to the increase of the activation of the prefrontal cortex and limbic system in the chronic pain population; increased activation of the anterior cingulate cortex, anterior insular cortex, and decreased thalamic activation in healthy individuals following cognitive strategies; in addition to increased activity in pre-frontal ventricular regions following prayer-based cognitive therapy. The methodological evaluation showed a moderate risk of bias, with great heterogeneity that made impossible a meta-analysis. Conclusion: Cognitive therapies modulate the intensity and affective experience of pain and may be responsible for altering the functioning of brain regions in an extensive network, including non-predominantly nociceptive regions. The lack of standardization of interventions points to the need for new studies that evaluate the use of cognitive therapies as a complementary approach in health care.